Electropolymerisation of Catalytically Active PEDOT from an Ionic Liquid on a Flexible Carbon Cloth Using a Sandwich Cell Configuration1. Issue 1 (4th November 2014) - Abdelhamid, Muhammad E.; Snook, Graeme A.; O'Mullane, Anthony P.
Abstract: The electropolymerisation of poly(3, 4‐ethylenedioxythiopene) (PEDOT) from an ionic liquid, butyl‐methylpyrrolidinium bis(trifluoromethanesulfonyl)imide (C4 mpyrTFSI), onto flexible carbon cloth electrodes is reported. A continuous, homogeneous and well‐adhered coating of the individual cloth fibres is achieved by employing a sandwich cell arrangement in which the carbon cloth, which is soaked with electrolyte, is placed between two indium tin oxide electrodes isolated from each other by a battery separator. The resultant PEDOT‐modified carbon cloth electrode demonstrates excellent activity for the oxygen reduction reaction, which results from the doping level, conductivity and morphology of the PEDOT layer, and is also tolerant to the presence of methanol in the electrolyte. This simple approach therefore offers a route to fabricate flexible polymer electrodes that could be used in various electronic applications. Abstract : Taking the cloth : The electropolymerization of poly(3, 4‐ethylenedioxythiophene) from the ionic liquid butyl‐methylpyrrolidinium bis(trifluoromethanesulfonyl)imide on flexible carbon cloth electrodes is reported (see figure). Compact films with high doping levels and conductivity are fabricated that demonstrate catalytic activity over a wide pH range for the oxygen reduction reaction, which is also tolerant to the presence of methanol.